2013
DOI: 10.1111/nure.12024
|View full text |Cite
|
Sign up to set email alerts
|

Use of natural AhR ligands as potential therapeutic modalities against inflammatory disorders

Abstract: The aim of this review is to discuss research involving ligands for the aryl hydrocarbon receptor (AhR) and their role in immunomodulation. While activation of the AhR is well known for its ability to regulate the biochemical and toxic effects of environmental chemicals, more recently an exciting discovery has been made indicating that AhR ligation can also regulate T-cell differentiation, specifically through activation of Foxp3+ regulatory T cells (Tregs) and downregulation of the proinflammatory Th17 cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
160
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 153 publications
(163 citation statements)
references
References 184 publications
(339 reference statements)
3
160
0
Order By: Relevance
“…AhR can also cross-talk and directly interact with proteins involved in major redox-regulated signalling pathways such as NF-kappaB and various kinases, such as Src, JNK, p38, MAPK and with oestrogen receptors to mediate oestrogen metabolism [61]. Recent studies have unraveled unsuspected physiological roles and novel alternative ligand-specific pathways for this receptor that allowed for hypothesising numerous pharmacological roles of AhR ligands useful for the development of a new generation of photo-protective drugs and cosmetics [62,63].…”
Section: Metabolic Barrier Of Human Skinmentioning
confidence: 99%
“…AhR can also cross-talk and directly interact with proteins involved in major redox-regulated signalling pathways such as NF-kappaB and various kinases, such as Src, JNK, p38, MAPK and with oestrogen receptors to mediate oestrogen metabolism [61]. Recent studies have unraveled unsuspected physiological roles and novel alternative ligand-specific pathways for this receptor that allowed for hypothesising numerous pharmacological roles of AhR ligands useful for the development of a new generation of photo-protective drugs and cosmetics [62,63].…”
Section: Metabolic Barrier Of Human Skinmentioning
confidence: 99%
“…Based on these results, interference with AHR-mediated signaling could yield therapeutic effects in psychiatric disorders (Busbee et al, 2013;Linden et al, 2010;Quintana, 2013).…”
Section: Aryl Hydrocarbon Receptor Signalingmentioning
confidence: 99%
“…More recently, the use of plant-derived indoles, such as 3,39-diindolylmethane (DIM), which are found in cruciferous vegetables, and other similarly structured compounds, have been reported as a potential therapeutic modality against inflammatory disorders (Busbee et al, 2013). Data from various cancer studies, which include prostate (Nachshon-Kedmi et al, 2003), colon (Lerner et al, 2012), and gastric (Li et al, 2013) cancers, have collectively suggested that DIM also acts on a number of molecular pathways centered on cellular proliferation and survival to mediate its effects.…”
Section: Introductionmentioning
confidence: 99%